PENGARUH PROMOSI, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Sarjita Sarjita (Jurnal Bisnis, Manajemen, dan Akuntansi, 2019)
This study aims to examine the effect of partial promotions on purchasing decisions, the effect of prices on purchasing decisions, the effect of product quality on purchasing decisions and to test the effect of simultaneous promotion, price and product quality on purchasing decisions. The population in this study were consumers who used Vaseline hand and body lotion to students in Yogyakarta, with a sample of 60 consumers of Vaseline hand and body lotion products. The data analysis method used in this study is the Convenience sampling method, and multiple linear regression analysis. Data processing is done using SPSS version 20.0 for Windows computer software. The results of the study show that partially the promotion variable does not affect consumer purchasing decisions, the price variable does not affect consumer purchasing decisions, the product quality variable has a effect on consumer purchasing decisions. And simultaneously promotion variables, prices and product quality do not affect consumer purchasing decisions. In addition, promotion factors, price and product quality contribute 53.8% to consumer purchasing decisions. While the remaining 46.2% is influenced by other factors not examined in this study, such as brand image and customer loyalty.